Pointing : where language, culture, and cognition meet - Kita, Sotaro, 1963- (L. Erlbaum Associates, 2003)
This volume brings together papers on pointing gestures from disciplines, such as developmental psychology, psycholinguistics, sign-language linguistics, lingiustic anthropology, conversational analysis and primatology.